2017
DOI: 10.1111/hae.13280
|View full text |Cite
|
Sign up to set email alerts
|

Defective acid hydrolase secretion in RUNX1 haplodeficiency: Evidence for a global platelet secretory defect

Abstract: Background RUNX1 haplodeficiency is associated with thrombocytopenia, platelet dysfunction and a predisposition to acute leukemia. Platelets possess three distinct types of granules and secretory processes involving dense granules (DG), α–granules and vesicles or lysosomes containing acid hydrolases (AH). DG and granule deficiencies have been reported in patients with RUNX1 mutations. Little is known regarding the secretion from acid-hydrolase containing vesicles. Methods and Results We studied two related p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…14,15 In this study Thrombocytopenia with normal platelet volume occurs in many, but not all, FPD/AML patients, 14,16,31,33 while a varying degree of platelet dysfunction is present in most affected patients. 34,35 Consistent with this, we found RUNX1 L43S/L43S mice to have mild thrombocytopenia, with unaffected platelet size, compared with RUNX1 WT/L43S and RUNX1 WT/WT animals. Our in vitro megakaryopoiesis experiments suggested that the reduced platelet count is related to a slightly delayed MK maturation during the middle stages of megakaryopoiesis in RUNX1 L43S/L43S mice.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…14,15 In this study Thrombocytopenia with normal platelet volume occurs in many, but not all, FPD/AML patients, 14,16,31,33 while a varying degree of platelet dysfunction is present in most affected patients. 34,35 Consistent with this, we found RUNX1 L43S/L43S mice to have mild thrombocytopenia, with unaffected platelet size, compared with RUNX1 WT/L43S and RUNX1 WT/WT animals. Our in vitro megakaryopoiesis experiments suggested that the reduced platelet count is related to a slightly delayed MK maturation during the middle stages of megakaryopoiesis in RUNX1 L43S/L43S mice.…”
Section: Discussionsupporting
confidence: 82%
“…38 However, these findings are different from the reduced secretion of the α-and d-granules observed in many FPD/AML patients. 34 Defective fibrinogen/JONA binding and spreading in fibrinogen in mutant mice indicated that the deleterious effect of p.Leu43Ser affects α IIb β 3 integrin insideout and outside-in signaling, respectively. It is worth mentioning that abnormal integrin α IIb β 3 activation has been previously reported in FPD/AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…While 9% of our index cases (representing 2 families) had probable pathogenic TF mutations affecting RUNX1 , 1 had no family history of leukemia or myelodysplasia. RUNX1 mutations alter gene expression, 19,37‐43 and we found reduced expression of PF4 , MYL9 , and ALOX12 in platelets from PFD participants with RUNX1 haploinsufficiency mutations, with some but not all showing increased MYH10 transcript and protein levels compared to controls. Accordingly, we caution against analyzing MYH10 for diagnostic purposes.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, thrombin induced free arachidonic acid release was unaffected in two patients with a RUNX1 mutation identical to that of the present patient. 31 Thus, the reported effects of inhibiting PCTP on platelet responses 2 are unlikely due to decreased thromboxane production.…”
Section: Discussionmentioning
confidence: 99%